The Development of Find The Object Game Application as The Media of English Vocabulary Learning for Second and Third Grades of Elementary School - Haris Setyawan; Bhaskara Satrya Priwandhana; Reza Giga Isnanda (Universitas Muhammadiyah Yogyakarta, 2020)
English is the language of international communication, which is why most countries in the world learn it. Therefore, we need to understand and be capable of communicating in English. Today’s English learning is mostly delivered by a lecture method. Moreover, there is no English vocabulary learning media in the form of application. Therefore, this research aims to develop a game application called “Find the Object” to help elementary school students learn English vocabulary by making the learning process more fun and interesting. The pre-test, post-test, and poll results revealed that this game significantly succeeded in increasing the English vocabulary of elementary school students. It was proven through the values of tests tending to increase after playing this game, and students felt more interested in learning English vocabulary.